De Novo Duplication of Chromosome 9p in a Female Infant: Phenotype and Genotype Correlation - Leone, Paola E.; Pérez-Villa, Andy; Yumiceba, Verónica; Hernández, María Ángeles; García-Cárdenas, Jennyfer M.; Armendáriz-Castillo, Isaac; Guerrero, Santiago; Guevara-Ramírez, Patricia; López-Cortés, Andrés; Zambrano, Ana Karina; García, Juan Luis; Hernández, Jesús María; Paz-y-Miño, César (Journal of Pediatric Genetics, 2020)
Trisomy 9p syndrome is the fourth most frequent chromosome aberration seen in infants. Duplication of the critical region 9p22p24 leads to mental retardation, psychomotor delay, and craniofacial and digital anomalies. We report a 2-year-old Ecuadorian girl with Trisomy 9p syndrome. Although her phenotype shares characteristics of Noonan syndrome, Giemsa trypsin banding technique shows there is an extra chromosomal segment on chromosome 14, and array analysis shows that it belongs to a duplication of 38 Mb of 9p13.1p24.3. Fluorescence in situ hybridization analysis detected three signals from 9p chromosome. The duplication is de novo, being another unique case of the few reported in the literature.
Keywords: Trisomy 9p syndrome; de novo duplication; cytogenetic; fluorescence in situ hybridization; mapping array